Potential of Herbal Plants Against Mycobacterium Tuberculosis Infection - Hamidah Retno Wardani; Destia Widyarani; Rany Agustin Wulandari; Damon Wicaksi (D'Nursing and Health Journal (DNHJ), 2020)
Introduction: Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis. The leading cause of death worldwide is responsible for 1.5 million deaths each year. The cause of tuberculosis infection is the tubercle bacillus discovered by Robert Koch in 1882. The organism causing it is Mycobacterium tuberculosis.The spread of new cases is divided in several regions including Southeast Asia and Africa, which are the regions that have the biggest contribution to the prevalence of tuberculosis. So it takes pillars and components of TB control that cover all lines. Method: This study aims to discuss the potential of herbal plants spread in Indonesia as herbal medicines that have the potential to treat tuberculosis infection. This study uses a literature study method which prepares the same as other research, but the sources and methods of data collection are by taking data from the library, reading, taking notes, and processing research materials. Result: One of the components that are currently being developed in TB infection intervention methods is the development of herbal medicines for tuberculosis control. The herbal medicines used come from garlic (Allium sativum), Centellaasiatica, beluntas leaves, Hibiscus rosasinensis L., Boechmeria virgate (Forst) Guill, tobacco leaves, Morindacitrifolia L., Javanese wood bark, Spondiaspinnata (Lf)Kurz. Conclusion: The herbal medicinal ingredients contain major chemicals such as alicin, ajoene, asiaticoside, asiatic acid, madecassic acid, and madecassoside, alkaloids, flavonoids, tannins, saponins, phenolic, and triterpenoids which have the ability to have a bactericidal effect to kill the Mycobacterium tuberculosis bacteria.